Consumers’ perceptions and attitudes toward a novel labeling framework for underutilized crops: a cross-national comparison - Bassignana, Chiara Flora; Bairati, Lorenzo; Bruno, Valentina; Torri, Luisa (Frontiers in Sustainable Food Systems, 2025)
Underutilized crops (UCs) offer significant ecological, nutritional, and socio-cultural benefits, yet remain marginalized in mainstream food systems. This study investigated consumers’ knowledge and attitudes toward a potential label for UCs across three European countries: Italy, Portugal, and Germany. Through a cross-national online survey (n = 3,023), we examined consumers’ familiarity with the UC concept, perceived social, environmental, and economic benefits, trust in a potential UC label, and willingness to buy UC-labeled products. Statistical analyses, including Mann–Whitney U tests, Kruskal–Wallis tests with post-hoc comparisons, and ordinal logistic regression models, revealed that declared knowledge of UCs is associated with significantly higher perceived benefits and stronger purchase intentions. Trust in the UC label emerged as the most significant predictor of willingness to buy, followed by socio-demographic and value-based factors such as education level, ethical concern, and food label engagement. Participants viewed the UC label as more closely aligned with the organic label than with the quality schemes of protected geographical indications and protected designations of origins. These results underscore the potential of a dedicated UC label to raise awareness, enhance consumer trust, and support more biodiverse and resilient food systems. The development of such a label should be accompanied by targeted communication strategies and participatory design processes to reflect the multifaceted value of underutilized crops.